Diurnal Transcriptional Regulation of Endosymbiotically Derived Genes in the Chlorarachniophyte Bigelowiella natans - Suzuki, Shigekatsu (Genome Biol Evol, 2016)
Chlorarachniophyte algae possess complex plastids acquired by the secondary endosymbiosis of a green alga, and the plastids harbor a relict nucleus of the endosymbiont, the so-called nucleomorph. Due to massive gene transfer from the endosymbiont to the host, many proteins involved in plastid and nucleomorph are encoded by the nuclear genome. Genome sequences have provided a blueprint for the fate of endosymbiotically derived genes; however, transcriptional regulation of these genes remains poorly understood. To gain insight into the evolution of endosymbiotic genes, we performed genome-wide transcript profiling along the cell cycle of the chlorarachniophyte Bigelowiella natans, synchronized by light and dark cycles. Our comparative analyses demonstrated that transcript levels of 7,751 nuclear genes (35.7% of 21,706 genes) significantly oscillated along the diurnal/cell cycles, and those included 780 and 147 genes for putative plastid and nucleomorph-targeted proteins, respectively. Clustering analysis of those genes revealed the existence of transcriptional networks related to specific biological processes such as photosynthesis, carbon metabolism, translation, and DNA replication. Interestingly, transcripts of many plastid-targeted proteins in B. natans were induced before dawn, unlike other photosynthetic organisms. In contrast to nuclear genes, 99% nucleomorph genes were found to be constitutively expressed during the cycles. We also found that the nucleomorph DNA replication would be controlled by a nucleus-encoded viral-like DNA polymerase. The results of this study suggest that nucleomorph genes have lost transcriptional regulation along the diurnal cycles, and nuclear genes exert control over the complex plastid including the nucleomorph.